Kemampuan Menulis Kata Tulisan Arab Melayu Mahasiswa Program Studi Pendidikan Bahasa Indonesia FKIP Universitas Islam Riau - Mukhlis, Muhammad; Asnawi, Asnawi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
This study focuses on the ability to write words in Malay Arabic script. This research problem is formulated about the ability to write two syllables and lebid from two syllables in Malay Arabic script. The purpose of the study is to describe in detail the ability to write Malay Arabic words and apply proper word-writing principles in Malay Arabic script. This research is a field research with quantitative type. This research was conducted in Language Education and Literature Program Indonesia FKIP Islamic University of Riau. The method used to collect data is by the test technique. The data of this research is the result of word writing skill test and applying correct wording principle in Malay Arabic script obtained from randomly taken sample of research. Analyzing data is done with the mean technique. The result of this research concludes that the ability of writing Arabic Malay words of students of Indonesian Language and Literature Education Program, Faculty of Teacher Training and Education, Islamic University of Riau is categorized with percentage of 71.72%. Furthermore, the ability to write Malay Arabic words of the students of Indonesian Language and Literature Education Studies Program, Faculty of Teacher Training and Education, Islamic University of Riau based on two syllables categorized with a percentage of 72.09% and based on the word syuku words more than two words low category ie 64.36% .